Value-Based Quality Care for Breast Cancer: More Than Guidelines - GÜLLÜOĞLU, MAHMUT BAHADIR (GALENOS YAYINCILIK, 2021)
Although guidelines recommend some of the most expensive diagnostic methods and therapies, some patients do have the opportunity to use them, but some others have overused or misused such methods. The cost of cancer care is increasing, but the satisfaction levels of patients and healthcare workers have not increased in line with this rise. Value-based care for cancer, especially breast cancer, should be implemented. For this reason, all unnecessary screening, tests, treatments, and follow-up parameters should be avoided.
Keywords: Cancer; breast; value; quality; cost; HEALTH-CARE; AMERICAN SOCIETY; UNITED-STATES; FRAMEWORK; DRUGS; COST